Evaluasi Kinerja Diagnostik dan Pemasaran Tes ColoSTAT Berbasis Darah untuk Deteksi Dini Kanker Kolorektal di Indonesia - Munatsir Oteiba; Tantri Yanuar Rahmat Syah; Edi Hamdi; Muhammad Reza Hilmy (Yayasan Literasi Sains Indonesia, 2025)
This study aims to evaluate the diagnostic performance of the blood-based ColoSTAT test as an early detection method for colorectal cancer while analyzing the marketing aspects of the product in Indonesia. The ColoSTAT test offers a non-invasive approach with ease of sampling and potentially high accuracy in detecting colorectal cancer at an early stage. The ColoSTAT test is a non-invasive method that utilizes specific biomarkers in the blood to identify the presence of colorectal cancer. This study method involves testing blood samples in populations at risk of colorectal cancer at several hospitals in Indonesia, and comparing the ColoSTAT test results with clinical diagnostic standards such as colonoscopy and biopsy. Diagnostic performance parameters analyzed include sensitivity, specificity, positive predictive value, negative predictive value, and overall accuracy of the test. The results indicate that the ColoSTAT test has competitive diagnostic performance and strong market potential if supported by an appropriate marketing strategy. The technological and marketing implications of the ColoSTAT test include increasing colorectal cancer screening coverage, reducing the burden on primary healthcare services, and increasing the effectiveness of colorectal cancer control in Indonesia.